Causes of poor eye contact in infants: a population-based study - Mette Levinsen (BMC, 2021)
Abstract Background Establishing eye contact between infants and parents is important for early parent-child bonding and lack of eye contact may be a sign of severe underlying disease. The aim of the study was to evaluate the causes of poor or lacking eye contact in infants. Methods Cross-sectional study reviewing all referrals of infants ≤1 year of age from January 1rst, 2016 to December 31rst, 2018. Medical information was retrieved from patient files covering pregnancy, birth, diagnostic work-up and ocular parameters such as refraction, visual acuity and structural findings. Results We identified 99 infants with poor or lacking eye contact. The relative frequency of causes was neurologic disease 36.4% (36/99), delayed visual maturation 24.2% (24/99), ocular disease 21.2% (21/99) and idiopathic infantile nystagmus 4.0% (4/99). Fourteen infants had a visual function within age-related norms at first examination despite poor eye contact at the time of referral. Of the infants with available data, 18/27 (33.3%) with neurologic cause, 15/23 (65.2%) with delayed visual maturation and 9/21 (42.9%) with ocular cause had visual acuity within the age-related norm at latest follow-up (0-41 months). In 23 infants, a genetic cause was found. Conclusion Poor eye contact in infants may be a sign of severe underlying disease, such as neurological or ocular disease. Close collaboration between pediatric ophthalmologists and neuro-pediatricians are warranted in the management of these infants.